Adaptive resource allocation algorithms with QoS support based on network conditions using fuzzy logic system for IEEE 802.11n networks / Bakeel Hussein Naji Maqhat (Institute of Graduate Studies, UiTM, 2017)
In wireless local area network (WLAN), the primary concern is Quality of Service (QoS) support that aims to satisfy the diverse service requirements and to guarantee higher data rates allocation for different service classes. However, IEEE 802.11n standard does not specify a scheduling algorithm to guarantee QoS. The performance benefits of existing solutions in MAC layers often fall short of providing the QoS support, particularly, it is still experiencing additional access latency and bandwidth allocation disorder where errors occur, that leads flows backlogged. The aim of this thesis is to develop a fair and efficient packet scheduling and adaptive bandwidth allocation algorithms to support QoS for a diverse service class for A-MSDU aggregation in IEEE 802.11n network. This thesis presents four main contributions for QoS provisioning that are robust, scalable, and can be successfully implemented in WLAN networks. The first contribution is the AMS scheduling algorithm. The aim is to satisfy QoS requirements for time sensitive applications by exploiting the A-MSDU attributes and adopting the idea of enabling selective retransmission in our scheduling algorithm to obtain aggregation with small size to support time-sensitive applications and enable prioritization according to the QoS requirements of the traffic classes. The second contribution is an efficient bandwidth allocation algorithm for A-MSDU aggregation called Adaptive Scheduling based Embedded Fuzzy (ASEF) system. ASEF system is fully dynamic with fuzzy logic based approach and adaptive deadlinebased scheme for various service class traffics. The algorithm employs fuzzy logic control which is embedded in the scheduler. The function is to control and dynamically update the bandwidth required by the various service classes according to their respective priorities, maximum latency, and throughput…